Clinicopathological Significance of SCD Expression in Colon Adenocarcinoma: Association with Histological Grade and Exploratory Assessment in Relation to PCNA - Jerzy Z. Piecuch; Adam Piecuch; Marek Michalski; Magdalena Rynkiewicz; Natalia Matysiak; Magdalena Onyszczuk; Marlena Brzozowa-Zasada (Journal of Clinical Medicine, 2026)
Background/Objectives: Colon adenocarcinoma is a heterogeneous disease, and tumours of similar pathological stage may differ in their metabolic and proliferative characteristics. Stearoyl-CoA desaturase (SCD) is involved in lipid metabolic reprogramming and may reflect aspects of tumour biology. The main goal of this study was to analyse SCD expression and its associations with clinicopathological factors, particularly focusing on histological grade. The relationship between SCD and proliferating cell nuclear antigen (PCNA) was evaluated as a secondary objective. Methods: Public TCGA/UALCAN and CPTAC/UALCAN data were examined as supportive transcriptomic and proteomic observations. Immunohistochemical SCD and PCNA expression was assessed in 113 patients with colon adenocarcinoma, and SCD localisation was additionally examined by qualitative immunogold electron microscopy. Standardised SCD and PCNA scores were combined with equal weighting to generate a secondary exploratory z-score. Associations with clinicopathological characteristics were assessed using appropriate univariable analyses, while the relationship between SCD and PCNA and the potential incremental contribution of SCD beyond PCNA were examined using correlation and exploratory regression-based analyses. ROC analyses were used only as exploratory descriptions of statistical separation between predefined clinicopathological groups. Results: Observations from supportive public databases indicated that SCD expression was higher in tumour tissue compared to normal tissue at both the transcriptomic and proteomic levels. In the institutional cohort, SCD expression was elevated in tumour tissue relative to matched non-neoplastic mucosa and was associated primarily with histological grade but not with nodal status or pathological stage. SCD showed a modest positive correlation with PCNA. The secondary exploratory combined SCD–PCNA score was associated with histological grade and with nodal status but did not outperform PCNA alone. Adding SCD to PCNA provided only limited incremental information for G3 histology and no incremental value for nodal involvement. Conclusions: SCD is a tumour-associated metabolic marker in colon adenocarcinoma, with its strongest association observed for histological grade. The combined score should not be interpreted as a biological entity or superior biomarker.